STUDI KOMPETENSI PEDAGOGIK MAHASISWA MICROTEACHING PENDIDIKAN BAHASA INGGRIS IKIP PGRI MADIUN - Sari, Dwi Rosita; Kusumawardhani, Rahardian; Garjito, Rhesi Gabriela (IKIP PGRI MADIUN, 2015)
Teaching and learning process needs competence teacher in order to gain the highest achievement. A competence teacher is a teacher who has good competence, one of them is pedagogic competence. This good pedagogic competence will be formed from practicing process which is kept in a good micro practice. Related to that, this study purposes to (1) analyze students pedagogic competence in practicing micro; (2) analyze the obstacles which appear while process of practicing micro teaching; and 3) formulate solution precisely to solve those obstacles. This study used case study model and the object was English department students who fulfilled specific criteria and joined micro teaching class. Data collection techniques used in the form of observation, questionnaires, interviews and documentation of achievement . The data analysis used was descriptive qualitative method which contains data reduction , presented data and draws conclusions or verification. Researchers have gained some following conclusions : (1) pedagogical competence of the students is still low; (2) Some students problems: less of time management, less of creating and using the media, less of methods and models of innovative learning techniques; less fluently of spoken English, inactive in the classroom, were confused in preparing lesson plans and syllabus, lack of confidence when teaching practice (nervous), and lack of specific student handbook which contains detail guidelines of microteaching; (3) The solutions can be used to overcome the obstacles that arise in the process of microteaching are: create microteaching models which has spesific approach, students should be accompanied and guided well in making lesson plans, students need to improve self-esteem because important in classroom management, and the students have to improve the English language skills both oral and written .Â Keywords : Microteaching, Pedagogic Competence